2018
DOI: 10.1007/s00586-018-5646-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of coronal curve changes in forward bending posture: a 3D ultrasound study of adolescent idiopathic scoliosis patients

Abstract: Spine deformities of AIS patients vary with different postures. The patterns of changes in sitting and sitting forward bending postures are highly subject dependent. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…They further found that the prone position is the most effective to predict the initial effect of orthotic treatment on patients with AIS. 51 Jiang et al 52 used 3D ultrasound (Scolioscan) to investigate the effects of postural changes in spine deformity in the coronal plane of AIS patients and found that 3D ultrasound was able to demonstrate spine deformities. They concluded that these deformities of AIS subjects vary with different positions, and the patterns of changes in sitting or sitting forward bending positions are highly subject dependent.…”
Section: Three-dimensional Ultrasoundmentioning
confidence: 99%
“…They further found that the prone position is the most effective to predict the initial effect of orthotic treatment on patients with AIS. 51 Jiang et al 52 used 3D ultrasound (Scolioscan) to investigate the effects of postural changes in spine deformity in the coronal plane of AIS patients and found that 3D ultrasound was able to demonstrate spine deformities. They concluded that these deformities of AIS subjects vary with different positions, and the patterns of changes in sitting or sitting forward bending positions are highly subject dependent.…”
Section: Three-dimensional Ultrasoundmentioning
confidence: 99%
“…The reliability and validity of different coronal spinal ultrasound angle measurements were further investigated using the same ultrasound system, excellent correlations were found between ultrasound and Cobb measurement and no differences in reliability and validity were observed between the ultrasound angles based on the spinous processes and transverse processes (Brink et al 2018). The 3D ultrasound system were also demonstrated to provide reliable information of spinal flexibility and in-orthosis correction of patients with AIS in the prone position (He et al 2017) and the patterns of alternation of coronal curve changes of patients with AIS during forward bending (Jiang et al 2018). In a previous study, ultrasound was shown to be able to provide reliable sagittal measurement of spinal phantoms and a few human subjects (Lee et al 2019), however the sample size of the human subjects was too small and relatively long period was required for data acquisition.…”
Section: Introductionmentioning
confidence: 98%
“…There are several ways to test the effectiveness of the FED method in treating patients with idiopathic scoliosis. The most popular, but harmful due to radiation exposure, is a radiological examination, which is still the standard for diagnosing scoliosis [ 3 , 4 , 5 ]. Scoliosis patients can get 10 to 25 spinal X-rays over several years equating to a maximum 10 to 25 mGy of cumulative exposure.…”
Section: Introductionmentioning
confidence: 99%